Accountability in the Management of Village Funds under Law No. 6 of 2014: An Analysis of Good Governance Implementation - Tajudin, Tajudin; Hutasoit, Jones Andreas; Oktafiandri, Andini Namira (Rechtsvinding, 2025)
Accountability in village fund management remains a major governance issue in Indonesia, particularly concerning inconsistent reporting practices and limited community involvement. This study aims to examine the implementation of accountability principles in village fund management based on the mandates of Law No. 6 of 2014 concerning Villages. Using a qualitative approach, data were collected through document reviews, field observations, and interviews with key stakeholders involved in village financial administration. The findings reveal that the principles of accountability have been practiced through participatory meetings, transparent financial reporting, and visual documentation as evidence of public responsibility. Nevertheless, village funds remain largely allocated to physical infrastructure, with community participation still limited in terms of substantive oversight. The study concludes that strengthening the capacity of village officials, optimizing digital-based financial reporting systems, and encouraging more active citizen participation are crucial strategies to promote transparency, accountability, and sustainability in village fund governance.